Comparison of Tribological Properties of Stainless Steel with Hard and Soft DLC Coatings. (2015) - Owens, Ana Gasco; Brühl, Sonia; Simison, Silvia; Forsich, Christian; Heim, Daniel
Abstract: Stainless steels are widely used in chemical, petrochemical and food-processing industries due to their good anticorrosion properties. However, they generally exhibit poor tribological properties which limit their applications in tribocorrosive conditions. Surface modifications, like diamond-like carbon (DLC) coatings, can be an optimal technological solution to overcome this problem. These films have attracted considerable attention because of their outstanding mechanical and tribological properties, but they have a major drawback that is their high internal stresses and low thermal stability. The internal stresses and film hardness depend on the ratio sp 2 /sp 3, therefore, the film can be classified as hard or soft-DLC coatings depending on this ratio. In this work, different stainless steels (EN14301, EN14435 and EN12316) samples were DLC-coated by plasma assisted chemical vapor deposition. Hard and soft a-C:H:Si films (silicon containing amorphous hydrogenated carbon) were obtained. The films were characterized by wear and adhesion tests; the results show an increase of the practical adhesion at higher film thickness and this improvement would be more effective for harder substrates. Pin-on-disc tests showed that soft-DLC films tend to develop a better tribological behavior than hard-DLC films and it is not influenced by the film thickness or the type of stainless steel substrate. The influence on the tribological behavior of test parameters, such as slide velocity and load, varies with the coating type.